2020
DOI: 10.1093/clinchem/hvaa175
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Apparent Increase in dd-cfDNA Percentage in Clinically Stable Patients Between One and Five Years Following Kidney Transplantation

Abstract: Background Donor-derived cell-free DNA (dd-cfDNA) is reportedly a valuable tool for graft surveillance following kidney transplantation (KTx). Possible changes in dd-cfDNA(%) reference values over time have not been evaluated. For long-term monitoring after KTx, changes in host cfDNA might represent a biasing factor in dd-cfDNA(%) determinations. Methods Plasma samples were obtained (n = 929) 12–60 months after engraftment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 33 publications
1
38
0
Order By: Relevance
“…The cfDNA extraction yield from plasma of our group of KTx patients was similar to that previously reported for KTx patients (21) but lower than that reported for liver transplanted patients (28). We observed a higher cfDNA extraction yield from plasma of KTx patients compared to plasma cfDNA from apparently healthy individuals, which is in agreement with Schütz et al who also reported a higher total cfDNA in a group of KTx patients compared to a healthy control group or a group with other medical conditions (29).…”
Section: Discussionsupporting
confidence: 92%
“…The cfDNA extraction yield from plasma of our group of KTx patients was similar to that previously reported for KTx patients (21) but lower than that reported for liver transplanted patients (28). We observed a higher cfDNA extraction yield from plasma of KTx patients compared to plasma cfDNA from apparently healthy individuals, which is in agreement with Schütz et al who also reported a higher total cfDNA in a group of KTx patients compared to a healthy control group or a group with other medical conditions (29).…”
Section: Discussionsupporting
confidence: 92%
“…One patient exhibited very low total cfDNA below the fifth percentile of the reference population, leading to absolute quantification of 22 copies/mL, which is below the cutoff, whereas relative quantification was 1.42% and above the cutoff. 13 For this patient, a sound explanation for low total cfDNA was possible, being low leukocyte count due to chronic myeloid leukaemia (CML) and nilotinib treatment. Despite the fact that no repeated biopsy was performed, the clinical course suggested no ongoing activity of antibody-mediated rejection (AMR) in this patient at the time of dd-cfDNA measurement.…”
Section: Resultsmentioning
confidence: 97%
“…We suspect this in 1 case, where CML and nilotinib treatment led to a low leukocyte count of 4.6 × 10 9 /L, resulting in total cfDNA levels below the fifth percentile of the reference population. 13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations